A heat shock protein 70 of Trypanosoma congolense as a diagnositic antigen - Boulange, A.F.; Katende, J.; Authié, Edith (European Union, 2000)
A 69-kDa antigen of Trypanosoma congolense induces both IgM and IgG in experimentally infected cattle. Cloning and sequencing of the gene coding for this antigen revealed that it belongs to the heat shock protein 70 family (hsp70) and is homologous to mammalian immunoglobulin binding protein (BiP). Due to its high antigenicity, the trypanosome BiP may be useful for developing an antibody-ELISA. Further-more, since defined regions of the molecule are conserved in different species of trypanosomes, while others are specific for T. congolense, it may be possible to develop both a test with broad specificity (pan-trypanosome) and a T. congolense-specific test. In order to assess the diagnostic potential of the trypanosome BiP, seven recombinant fragments were expressed in a bacterial expression system. Preliminary tests were carried out using a recombinant truncated protein (C-25) as the antigen, with forty sera taken during T. congolense experimental infections. All 22 sera from infected cattle gave O.D. values above those given by sera from 18 non-infected cattle. Sera collected sequentially during experimental infections were then compared for their reactivity to a crude lysate or to C-25. The C-25 based assay was of low sensitivity in primary infections, but detected most positive samples during rechallenge infections. The disappearance of anti-C-25 IgG after trypanocidal treatment was faster than that of IgG to a T. congolense crude extract. Although further evaluation of C-25 is required, particularly as regards specificity, this antigen is one of the very few defined candidate antigens for the Development of a standardisable antibody-ELISA.